EFFORTS TO IMPROVE COMMUNITY PHYSICAL AND MENTAL HEALTH AS A STEP TO ACCELERATE ACHIEVING SUSTAINABLE DEVELOPMENT GOALS (SDGS) IN RINGINSARI VILLAGE, KEDIRI REGENCY - Wijayanti, Dini Prastyo; Rohmawati, Nina Rizka; Dewanti, Nisa; Sulistyowati, Agus; Nurcahyaningtyas, Widya; Riesmiyatiningdyah; Listari, Risti Puji; Widati, Amila (Community Service Journal of Indonesia, 2024)
Counseling activities were given to students of SD Negeri Ringinsari II and participants at the Integrated Primary Service Post in Ringinsari Village, Kandat District, Kediri Regency, as a form of community service in the form of delivering materials and simulations that are expected to increase public awareness of health and welfare. Counseling activities were carried out in September in two locations, namely SD Negeri Ringinsari II and the Integrated Primary Service Post. Before carrying out counseling activities, a preparation process was carried out for approximately four weeks before the implementation of the activity, starting from determining the type of activity to submitting permits to the relevant parties. As a form of evaluation, this activity was attended by all participants, the participants participated in the activities with great enthusiasm and the counseling guidance activities ran smoothly.